2003
DOI: 10.1159/000071122
|View full text |Cite
|
Sign up to set email alerts
|

A Pilot Randomized Trial of Induced Blood Pressure Elevation: Effects on Function and Focal Perfusion in Acute and Subacute Stroke

Abstract: Background: Small, unrandomized studies have indicated that pharmacologically induced blood pressure elevation may improve function in ischemic stroke, presumably by improving blood flow to ischemic, but noninfarcted tissue (which may be indicated by diffusion-perfusion mismatch on MRI). We conducted a pilot, randomized trial to evaluate effects of pharmacologically induced blood pressure elevation on function and perfusion in acute stroke. Methods: Consecutive series of patients with large diffusion-perfusion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
139
0
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 215 publications
(145 citation statements)
references
References 20 publications
(25 reference statements)
4
139
0
2
Order By: Relevance
“…Results of our study supported that phenylephrine inducedhypertension is a beneficial way to restore motor progression in patients with progressing lacunar infarction, concurring with prior studies [5,[13][14][15][16][17]21]. There has been no clear explanation on the mechanism of progressing lacunar infarction and motor recovery after induced hypertension [5,[22][23][24][25].…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…Results of our study supported that phenylephrine inducedhypertension is a beneficial way to restore motor progression in patients with progressing lacunar infarction, concurring with prior studies [5,[13][14][15][16][17]21]. There has been no clear explanation on the mechanism of progressing lacunar infarction and motor recovery after induced hypertension [5,[22][23][24][25].…”
Section: Discussionsupporting
confidence: 88%
“…Hillis et al restored the BP of an aphasic patient and the symptoms improved due to reperfusion of the Wernicke's area [5]. A randomized prospective pilot study using induced-hypertension also showed that significant improvement of NIHSS, cognitive score and volume of hypoperfused tissue on perfusion-weighted imaging [15]. Various studies have pointed out the existence of perfusion defects in lacunar infarction, and a recent report revealed that mean systolic BP was lower in early deteriorating patients with abnormal PWI [7,8,26].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations